Boron Induces Early Matrix Mineralization via Calcium Deposition and Elevation of Alkaline Phosphatase Activity in Differentiated Rat Bone Marrow Mesenchymal Stem Cells - Bent-al-hoda Movahedi Najafabadi; Mohammad Hussein Abnosi (Cell Journal, 2016)
Objective: Boron (B) is essential for plant development and might be an essential micronutrient for animals and humans. This study was conducted to characterize the impact of boric acid (BA) on the cellular and molecular nature of differentiated rat bone marrow mesenchymal stem cells (BMSCs). Materials and Methods: In this experimental study, BMSCs were extracted and expanded to the 3rd passage, then cultured in Dulbecco’s Modified Eagle’s Medium (DMEM) complemented with osteogenic media as well as 6 ng/ml and 6 μg/ml of BA. After 5, 10, 15 and 21 days the viability and the level of mineralization was determined using MTT assay and alizarin red respectively. In addition, the morphology, nuclear diameter and cytoplasmic area of the cells were studied with the help of fluorescent dye. The concentration of calcium, activity of alanine transaminase (ALT), aspartate transaminase (AST), lactate dehydrogenase (LDH) and alkaline phosphatase (ALP) as well as sodium and potassium levels were also evaluated using commercial kits and a flame photometer respectively. Results: Although 6 μg/ml of BA was found to be toxic, a concentration of 6 ng/ml increased the osteogenic ability of the cell significantly throughout the treatment. In addition it was observed that B treatment caused the early induction of matrix mineralization compared to controls. Conclusion: Although more investigation is required, we suggest the prescription of a very low concentration of B in the form of BA or foods containing BA, in groups at high risk of osteoporosis or in the case of bone fracture.